2002
DOI: 10.1038/sj.ijo.0801847
|View full text |Cite
|
Sign up to set email alerts
|

WHO and ADA criteria for the diagnosis of diabetes mellitus in relation to body mass index. Insulin sensitivity and secretion in resulting subcategories of glucose tolerance

Abstract: OBJECTIVE:To determine the influence of body mass index (BMI) on agreement between the American Diabetes Association (ADA) and the new World Health Organization diagnostic criteria for the diagnosis of diabetes mellitus and to investigate the metabolic profile of the resulting subcategories. DESIGN: Cross-sectional study SUBJECTS: A total of 3018 subjects with no previous history of diabetes and fasting glucose < 7.8 mmol=l, with a wide range of BMIs. MEASUREMENTS: (1) Prevalence of impaired glucose regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…This is consistent with the observations of other comparisons of the ADA to WHO criteria. For example, the 10 most recent studies we identified in which the ADA criteria were compared with other criteria, the sensitivity ranged from as low as 31% in a an obese French population to as high as 79% in Canarian Caucasians (13,14,(25)(26)(27)(28)(29)(30)(31)(32) (Table 6). We identified two cut-off values (fasting plasma glucose Ն5.7 mmol/l and an HbA 1c Ն5.9%) that minimize the number of false positives and false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the observations of other comparisons of the ADA to WHO criteria. For example, the 10 most recent studies we identified in which the ADA criteria were compared with other criteria, the sensitivity ranged from as low as 31% in a an obese French population to as high as 79% in Canarian Caucasians (13,14,(25)(26)(27)(28)(29)(30)(31)(32) (Table 6). We identified two cut-off values (fasting plasma glucose Ն5.7 mmol/l and an HbA 1c Ն5.9%) that minimize the number of false positives and false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…There are different pathogenic mechanisms underlying IPD and T2DM (FPG Ն126 mg/dL [Ն7.0 mmol/L] and 2-h PG Ն200 mg/dL [Ն11.1 mmol/L]) (17 ). IPD is characterized by increased peripheral insulin resistance and reduced first-phase insulin secretion, and T2DM by progressive increase in peripheral and hepatic insulin resistance and reduced basal and first-phase insulin secretion (17 ), signifying that T2DM is a more serious metabolic disturbance than IPD. We detected higher insulin concentrations in T2DM than IPD cases (Table 1), which may be the basis for more serious disorders of lipid, steroid hormone, and glucose metabolism in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Liver US and plasma levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), γ -glutamyl transpeptidase (γ -GT), blood glucose, and insulin were determined using commercial kits. Insulin resistance was calculated by the HOMA test [32]. Adverse events were evaluated from the questionnaire, which reported signs and symptoms graded from mild to severe, possible association of symptoms with the treatment, the method used for resolution, and the necessity to stop the treatment.…”
Section: Design Of the Studymentioning
confidence: 99%